Answer:
m=-3
x1,y1=1,-5
we have,
y-y1=m(x-x1)
y-(-5)=-3(x-1)
y+5=-3x+3
3x+y+2=0 is the required eqn
Answer:
d= -6
Step-by-step explanation:
56 = -8d + 8
1) You want to get d by itself. Subtract 8 from both sides.
56 = -8d + 8
- 8 - 8
<em>(8 - 8 = 0, and 56 - 8 is 48.)</em>
48 = -8d
2) Then, you divide my -8 on both sides.
(<em>48 / -8 is -6, and -8d / -8 is just d.)</em>
-6 = d
So, d = -6
<u>Answer:</u>
Below!
<u>Explanation:</u>
Exponents are small numbers that defines how many times does the base needs to multiply itself. Two exponents can also be classified in words. 'Squared' defines a number multiplying itself two times. 'Cubed' defines a number multiplying itself three times. If there is a zero as the base's exponent, this means that the result will always be 1. Now, let's solve all the problems together.
- 2¹ = 2
- 3⁵ = 3 x 3 x 3 x 3 x 3 = 243
- 4³ = 4 x 4 x 4 = 64
- 6⁴ = 6 x 6 x 6 x 6 = 1256
- 7⁴ = 7 x 7 x 7 x 7 = 2401
- 1⁶ = 1 x 1 x 1 x 1 x 1 x 1 = 1
- 8² = 8 x 8 = 64
- 2³ = 2 x 2 x 2 = 8
- 4⁴ = 4 x 4 x 4 x 4 = 256
- 10³ = 10 x 10 x 10 = 1000
- 12² = 12 x 12 = 144
- 5⁴ = 5 x 5 x 5 x 5 = 625
- 6² = 6 x 6 = 36
- 3⁶ = 3 x 3 x 3 x 3 x 3 x 3 = 729
- 7³ = 7 x 7 x 7 = 343
- 2⁴ = 2 x 2 x 2 x 2 = 16
- 11⁰ = 1
- 4³ = 4 x 4 x 4 = 64
- 1¹² = 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 x 1 = 1
Hoped this helped!
A)
x 0 1 2 3 4
y 5 10 15. 20. 25
b) x 0 1 2 3. 4
y 1. 10. 37. 82. 145
Answer:
C
Step-by-step explanation:
i think because the bottom of the triangles are the denominators and the x is the numerator